M & A disputes : a professional guide to accounting arbitrations - Biemans, A. Vincent, 1977-; Hansen, Gerald M., 1967- (Wiley finance series, 2017)
With deep insight from experts in the field-including valuable advice from the arbitrator's perspective-this invaluable book guides you through the entire process to explore the variables at work. --